Designing an evidence-based working method for medical work disability prognosis evaluation–an intervention mapping approach - Snoeck-Krygsman, Sylvia P.; Donker-Cools, Birgit H. P. M.; Jansen, Lyanne P.; Hoving, Jan L.; Schaafsma, Frederieke G. (Frontiers in Public Health, 2023)
Purpose Performing evidence-based work disability prognosis evaluation (WDPE) of clients on sick leave is a difficult task for physicians. The aim was to develop a working method to support physicians in performing evidence-based WDPE and to improve WDPE quality. Materials and methods Intervention Mapping (IM) supplemented with elements of the Behavior Change Wheel (BCW) guided project planning for developing the working method. This approach allowed combination with other frameworks and, e.g., behavior change theories. WDPE quality challenges were analyzed on various ecological levels, e.g., the individual (i.e., the physician), interpersonal (i.e., the client) and organizational level, culminating into a multilevel logic model of the problem. Determinants that contributed to this problem, e.g., lack of physicians’ knowledge on performing evidence-based WDPE, were identified. Performance objectives were formulated that could contribute to a desired change in WDPE quality. From the performance objectives and determinants (e.g., knowledge), change objectives were derived. In order to achieve these change objectives, suitable intervention functions (e.g., education) and policy categories (e.g., service provision) were identified, allowing the formulation of intervention components. Behavior change techniques (e.g., feedback on outcomes of a behavior) were selected to serve the intervention functions to deliver the desired change. This led to the conceptualization of an intervention plan. Results The intervention “Prognosable” is presented. It consists of a stepwise working method (SWM) for evidence-based WDPE. The SWM offers an overview of important aspects (e.g., medical condition, clients’ confidence in return-to-work) to consider in individual clients’ WDPE. The SWM helps physicians to identify crucial functional limitations, find and appraise evidence-based information, weigh all relevant prognostic aspects and it supports physicians to conclude with an evidence-based WDPE, tailored to the individual client. The intervention “Prognosable” was designed, which also includes an educational program and a supportive software tool to enable implementation of the SWM. Conclusion IM combined with BCW elements guided the development of a SWM for evidence-based WDPE. The SWM will be delivered through an educational program for physicians supported by a digital tool. The SWM, educational program and digital tool are ready to be implemented and evaluated in practice as the intervention “Prognosable.”